The Impact of Cultural References on Modern Arabic Linguistics - Jaloul Daqi, Jaloul Daqi (El Omda in Linguistics and Discourse Analysis, 2019)
The impact of cultural references in modern Arabic Linguistics -Form of Arab thought struggle through the ages even suggest currents, stream strives to maintain the Arab heritage, and modernist stream tries to adopt the Western path and emulate.Since the Arabic language lesson in General, and the lesson of tongue in particular are an integral part of this activity is thought to have already undergone undergone this thought of conflict with different terms, from alflologi down to old perceptions perception formed by ancient Arabic linguistic theory.In the chaos of this tugging, and intersections, lingual lesson tried to build himself an independent structure itself away from cultural references. Judging from this, this study seeks to determine the impact of these cultural references on the lingual lesson in Arab intellectual conflict between supporters of the conservative and modernist stream and monitor positions and informing the Arab tongue lesson in light of this conflict.